2D amphiphilic organoplatinum(ii) metallacycles: their syntheses, self-assembly in water and potential application in photodynamic therapy. Issue 58 (3rd July 2018) - Yao, Yong; Zhao, Ruibo; Shi, Yujun; Cai, Yan; Chen, Jiao; Sun, Siyu; Zhang, Wei; Tang, Ruikang
Abstract : Two 2D amphiphilic metallacycles with a porphyrin unit as the core and hydrophilic glycol units as the tail were designed and fabricated successfully. They can self-assemble into micelles in water and have potential applications in photodynamic therapy. Abstract : Two 2D amphiphilic organoplatinum(ii ) metallacycles with a porphyrin unit as the core and hydrophilic glycol units as the tail were designed and fabricated successfully through a new method called "coordination-driven self-assembly". They can self-assemble into micelles in water and have potential applications in photodynamic therapy.